Take the plunge: Using phraseology to enhance learners’ knowledge of grammar - Garcia Rosa, Rodrigo (BELT - Brazilian English Language Teaching Journal, 2023)
Phraseology has proven to be an important aspect of languages; as such, linguistic theories were forced to reshape their explanatory tools so as to incorporate this important aspect of language to their descriptive models. In light of this, analogous areas such as first and second language acquisition theories have all acknowledged the importance of speakers’ phraseological knowledge in real communication, both in L1 and L2 acquisition settings and in general language use. Nevertheless, despite being a relatively well-known phenomenon in theoretical studies, little has been said about the relationship between phraseology and syntax. More specifically, the idea of using phraseology as a starting point for the teaching of schematic grammatical structures seems to be a promising area of application and investigation. This paper aims to contribute to this area by presenting some ideas on how phraseology can be used as a springboard for the teaching of grammar.